Obstetric and neonatal outcomes of pregnant women with severe mental illness at a specialist antenatal clinic - Nguyen, T.; Faulkner, D.; Frayne, J.; Allen, S.; Hauck, Yvonne; Rock, D.; Rampono, J. (Australasian Medical Publishing Company Pty. Ltd., 2012)
Objective: To evaluate the obstetric and neonatal outcomes of pregnant women with severe mental illness (SMI) who attended a specialist multidisciplinary antenatal clinic in Perth, Western Australia. Design, setting and participants: A retrospective case-note audit of outcomes from the Childbirth and Mental Illness Antenatal Clinic (CAMI clinic) at King Edward Memorial Hospital for pregnant women with severe mental illness (SMI), aged 18–41 years, who gave birth between December 2007 and April 2011, and their babies. Main outcome measures: Obstetric and neonatal outcomes for 138 women and newborns from singleton live births. Data were compared between three diagnostic groups (schizophrenia, bipolar and non- sychotic SMI), and with WA obstetric and perinatal statistics for 2008. Results: 44 women with schizophrenia, 56 with bipolar disorder and 38 with non-psychotic SMI attended antenatal care for an average of 7.7 (SD, 3.3) visits. The proportion of women who smoked tobacco was significantly higher than that in the WA antenatal population (46% v 15%; P< 0.0001). Alcohol use, illicit substance use and psychotropic medication exposure during pregnancy were high. The women were at increased risk of developing gestational diabetes mellitus (15% v 4%; P < 0.0001) and pre-eclampsia (9% v 3%; P < 0.0001), and birth complications were more common. Babies born to CAMI clinic women were less likely to have Apgar scores ≥ 8 at 1 minute and 5 minutes. Pregnant women with schizophrenia had more psychiatric relapses during pregnancy, and had more statutory child welfare involvement. Gestational age at birth and infant birth weights were similar for the pregnant women with SMI and the WA population in 2008.Conclusions: Women attending our specialist clinic had increased rates of obstetric and neonatal complications compared with the general population, and were exposed to a cluster of risk factors. We report encouraging trends in antenatal attendance, gestational age at birth, and birth weights. Managing pregnant women with SMI will require a comprehensive approach aimed at early detection of obstetric complications and psychosocial difficulties, as well as neonatal monitoring. Optimising prepregnancy maternal health and welfare may also be of benefit.